The Role of Adenosine A1 and A2a Receptors in Cerebral Blood Vessel Reactivity of Sprague Dawley Rats Exposed to Hyperbaric Oxygenation - Vedran Đambić; Zrinka Mihaljević; Ines Drenjančević; Ivana Jukić; Petar Šušnjara; Aleksandar Kibel (Molecules, 2025)
Hyperbaric oxygenation (HBO2) can modify gene and protein expression, signaling pathways, and vascular function, leading to altered vasomotor responses. Adenosine receptors (ARs) may mediate these effects by modulating vasoactivity. This study investigated flow-induced dilation (FID) and hypoxia-induced dilation (HID) in the presence or absence of A1R/A2aR agonists (CCPA and CGS-21680, respectively) and antagonists (DPCPX and SCH-58261, respectively) in isolated middle cerebral arteries (MCAs) from Sprague Dawley rats of both sexes and the direct dose-dependent effects of A1R and A2aR agonists on the vascular reactivity of MCAs. Rats were exposed to either acute HBO2 (Ac-HBO2) or intermittent HBO2 over four days (In-HBO2). Ac-HBO2 impaired vascular responses to A1R and A2aR agonists and significantly decreased FID and HID. In both Ac-HBO2 and In-HBO2, A1R modulation did not significantly affect FID or HID. A2aR stimulation reduced FID in the In-HBO2 group, while A2aR antagonism had no significant effect on HID. However, the A2aR agonist’s presence enhanced HID in In-HBO2-exposed rats. Protein expression of A1R and A2aR decreased after Ac-HBO2, while gene expression increased following In-HBO2. These findings suggest that ARs play a role in HBO2-induced vasoreactivity, which possibly changes in MCA, potentially via the modulation of ARs gene and protein expression.